2014
DOI: 10.1093/ntr/ntu141
|View full text |Cite
|
Sign up to set email alerts
|

Correlates and Prevalence of Menthol Cigarette Use Among Adults With Serious Mental Illness

Abstract: Individuals with SMI-particularly those who are younger, have racial/ethnic minority status, and have been diagnosed with a psychotic disorder-are vulnerable to menthol cigarette use. FDA regulation of menthol may prevent initiation and may encourage cessation among smokers with SMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Findings from studies with unadjusted analyses are consistent with results from the adjusted analyses and are cross-referenced, as applicable, below. These results, as detailed in Table 2, include no difference in HSI based on data from NHANES and TUS-CPS, among both adult and youth smokers; 44 lower mean HSI score for menthol compared to smokers of unflavored cigarettes among 10,760 adult smokers from eight European countries; 67 no statistically significant difference in mean FTND scores among menthol versus nonmenthol smokers in the TES; 6 no statistically significant difference in FTND score among smokers with serious mental illness; 50 no statistically significant difference between menthol and nonmenthol smokers for NDSS or FTND mean scores in the multi-ethnic sample of young adults in Hawaii described above; 46 and no difference in FTND scores among a stratified inpatient sample of menthol and nonmenthol smokers. 62 The remaining available studies report on dependence measures in a variety of samples.…”
Section: Validated and Widely Accepted Dependence Measuresmentioning
confidence: 94%
See 2 more Smart Citations
“…Findings from studies with unadjusted analyses are consistent with results from the adjusted analyses and are cross-referenced, as applicable, below. These results, as detailed in Table 2, include no difference in HSI based on data from NHANES and TUS-CPS, among both adult and youth smokers; 44 lower mean HSI score for menthol compared to smokers of unflavored cigarettes among 10,760 adult smokers from eight European countries; 67 no statistically significant difference in mean FTND scores among menthol versus nonmenthol smokers in the TES; 6 no statistically significant difference in FTND score among smokers with serious mental illness; 50 no statistically significant difference between menthol and nonmenthol smokers for NDSS or FTND mean scores in the multi-ethnic sample of young adults in Hawaii described above; 46 and no difference in FTND scores among a stratified inpatient sample of menthol and nonmenthol smokers. 62 The remaining available studies report on dependence measures in a variety of samples.…”
Section: Validated and Widely Accepted Dependence Measuresmentioning
confidence: 94%
“…6,36,44,46,49,50,51,62,67,75,84,86,98,102,[108][109][110][111][112] Many of the newly identified analyses report no difference in TTFC among menthol and nonmenthol smokers overall and in a number of subgroups. 36,46,49,50,62,86,98,102,[108][109][110] Studies supporting that menthol smokers have the same or later TTFC as nonmenthol smokers include numerous publications from large or representative studies with adjusted results 6,36,44,49,67,79,107,109,110 and unadjusted results from other large or representative surveys. 73,87,89,91,93,96 Some publications have reported discordant TTFC results (i.e., no difference and longer or shorter TTFC).…”
Section: Smoking Frequencymentioning
confidence: 98%
See 1 more Smart Citation
“…The cooling and soothing sensation of menthol cigarette smoking, which masks the harshness of inhaled cigarette smoke [14, 15], increases the rewarding and sensory properties of menthol smoking beyond those of nicotine alone and may be particularly appealing to individuals with substance use or mental health problems. Both Hickman et al 2014 and Young-Wolff and colleagues (2015) found an elevated prevalence of menthol cigarette smoking among individuals with psychological distress [16, 17]; while Cohn et al 2016 found higher rates of depression and anxiety in a national sample of young adult menthol tobacco users, relative to non-menthol tobacco users [18]. Further, qualitative work suggests that menthol cigarettes may heighten drug-related high and help to sustain euphoric mood [19].…”
Section: Introductionmentioning
confidence: 99%
“…Kiviniemi et al 2010 found that psychological distress was correlated with higher smoking prevalence and increased odds of poor cessation outcomes among White, but not Black smokers [25]. However, menthol cigarettes are disproportionately used by Black smokers [26], and research shows elevated rates of psychological distress among menthol cigarette smokers relative to non-menthol smokers [16, 17]. However, there are no studies of differences across Black and White menthol and non-menthol smokers on mental health factors.…”
Section: Introductionmentioning
confidence: 99%